2015
DOI: 10.4048/jbc.2015.18.3.218
|View full text |Cite|
|
Sign up to set email alerts
|

Lentivirus-Mediated Short-Hairpin RNA Targeting Protein Phosphatase 4 Regulatory Subunit 1 Inhibits Growth in Breast Cancer

Abstract: PurposeProtein phosphatase 4 regulatory subunit 1 (PP4R1), as an interaction partner of the catalytic serine/threonine-protein phosphatase 4 catalytic subunit has been shown to involve in cellular processes and nuclear factor κB signaling. However, the functions of PP4R1 in human breast cancers remain unclear. This study is designed to explore the effect of PP4R1 knockdown on the biological characteristics of breast cancer cells.MethodsA lentivirus-mediated short hairpin RNA (shRNA) was designed to knockdown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…At the early stage, PPPases were simply identified as tumor suppressor proteins or oncogenic proteins. In recent years, accumulating evidence has indicated that PPPases play different roles in distinct cancers, which may be due to the diversity of regulatory subunits of PPPases. Here, we list a few examples, mainly involving PP1, PP2A, and PP4 to illustrate that PPPases could act as both tumor promoters and tumor suppressors in specific cancers (Figure B).…”
Section: Structure and Biological Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the early stage, PPPases were simply identified as tumor suppressor proteins or oncogenic proteins. In recent years, accumulating evidence has indicated that PPPases play different roles in distinct cancers, which may be due to the diversity of regulatory subunits of PPPases. Here, we list a few examples, mainly involving PP1, PP2A, and PP4 to illustrate that PPPases could act as both tumor promoters and tumor suppressors in specific cancers (Figure B).…”
Section: Structure and Biological Functionmentioning
confidence: 99%
“…For example, PR55α (a regulatory subunit) containing PP2A acts as a tumor promoter in pancreatic cancer by sustaining hyperactive tumor promoters, including YAP, AKT, ERK and Wnt; , PR61γ1 or PR61γ3 (PP2A regulatory subunit) containing PP2A acts as a tumor suppressor to stabilize p53 by dephosphorylating at either Ser37 or Thr55. , PP4 is also well-studied, and it play the opposite role in different cancers with different regulatory subunits. PPP4R1, a regulatory subunit of PP4, is overexpressed in many cancers, such as breast cancer, lung cancer, and hepatocellular carcinoma . PPP4R1 knockdown induces cancer cell proliferation inhibition by downregulating cell cycle activators .…”
Section: Structure and Biological Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…A PP4 hibás működése szerepet játszhat különböző rákos megbetegedések kialakulásában, onkogénként funkcionálhat petefészekrák [87], mellrák [31,88,89],…”
Section: Sejtciklus éS Sejtosztódásunclassified
“…Míg a PP4c túltermelés gátolja a proliferációt és csökkenti a mellrák sejtek metasztázisát, ezzel egyidőben növeli ezen sejtek apoptotikus aktivitástát a Bad és PEA-15 fehérjék defoszforilációján keresztül [89,95]. Ezekben a sejtekben a PP4R1 csendesítés szintén jelentősen gátolja a tumornövekedést és indukálja az apoptózist a PARP gátlásán és kaszpáz-3 aktiválása révén [88]. A PP4-nek nem csak a katalitikus és az R1, hanem az R2 alegysége is fontos a mellrák kialakulásában.…”
Section: Sejtciklus éS Sejtosztódásunclassified